2015
DOI: 10.1007/s40368-015-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous anaesthesia in children with 4 % articaine and epinephrine 1:400,000 using computer-assisted systems

Abstract: These results suggest that CAIO with 4 % articaine and epinephrine diluted 1:400,000 can be an alternative to usual infiltration techniques or IO with epinephrine at a higher concentration for most of treatments in primary and permanent teeth. Further studies are needed to evaluate its efficacy in permanent teeth in case of endodontic treatment or extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Previous papers about studies performed in children and adults using computer‐controlled needle rotation and injection suggested that IOA could be selected instead of CIA because the anaesthetic agent is injected directly in the cancellous bone close to the tooth needing to be anaesthetized, even for hot teeth such as MIH teeth . Although the difference in pain scores between IOA and CIA was statistically significant, it corresponded to less than one unit on the VAS, which limits its clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers about studies performed in children and adults using computer‐controlled needle rotation and injection suggested that IOA could be selected instead of CIA because the anaesthetic agent is injected directly in the cancellous bone close to the tooth needing to be anaesthetized, even for hot teeth such as MIH teeth . Although the difference in pain scores between IOA and CIA was statistically significant, it corresponded to less than one unit on the VAS, which limits its clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…To lessen the pain of the anesthetic effect's injection, anesthesia is administered using this approach at a steady velocity and pressure [42]. It consists of a handpiece and a control box; by depressing the pedal, signals are transmitted through Bluetooth to the main control box.…”
Section: Quicksleepermentioning
confidence: 99%
“…В отечественной стоматологии традиционно выделяют проводниковую анестезию (ориентированную на дентальное сплетение и нервные стволы) и, в противовес ей, инфильтрационную, или, точнее, супрапериостальную (ориентированную на нервные окончания), дополняя классификацию альтернативными/вспомогательными техниками с анатомическими названиями -внутрикостной/транскортикальной 6 , интралигаментарной, интрасептальной (часто эти четыре техники объединяют термином «внутрикостные»), внутрипульпарной [1], а также интрапапиллярной [10]. В последние годы предложено 6 Внутрикостная анестезия здесь не будет описана подробно, так как ее классический вариант в практике не востребуется, а компьютеризированные системы для внутрикостной анестезии малодоступны; в детской стоматологии описан положительный опыт применения последних в двух пилотных исследованиях: получен высокий эффект анестезии пульпы постоянных и временных моляров нижней челюсти малым объемом артикаина 4% (до 0,9 мл) с А в высоком разведении (1:400 000) [27]; доказана эффективность технологии при лечении нижнечелюстных постоянных моляров с гипоминерализацией (MIH) [29].…”
Section: техники/виды инъекционной анестезии с применением иглы для л...unclassified